(untitled) (Eurasian Medical Research Periodical, 2022)
This study aims to know the effects of spinal anaesthesia on the Study of total dynamics in pregnant women in Iraq were. This study was conducted in different hospitals in Baghdad, Iraq, where 80 patients were collected and divided into two groups, where each group included 40 patients to know the effect of spinal anaesthesia on hemodynamic in pregnant women. An elevation was found in Lowest SBP mmHg Compared to the control group; as for Lowest DBP mmHg, we note the rise and the effect of spinal anaesthesia on patients, where the value of sedation was 70.3±13.8 As for the control group, it was 45.6 ± 9.1. The relationship generated by the effect of spinal anaesthesia on the patients and the group was clarified, and we note that there is a clear and positive effect on the group of patients. As for the control group, the type of effect was negative, and no statistically significant relationship was found.